EXAMINING THE PREDICTIVE RELATIONSHIP BETWEEN EMPLOYEE WORK MOTIVATION AND PERSONNEL INDIVIDUAL WORK PERFORMANCE: THE ROLE OF JOB SATISFACTION AND JOB STRESS - Ofobruku, Goodluck (African Journal of Social and Behavioural Sciences, 2023)
The purpose of this study was to investigate the relationship between employee work motivation and individual work performance, as well as the impact of job satisfaction and job stress on this relationship. The design of this study was cross-sectional, and data were collected with self-report measures. One hundred and ninety-five employees were drawn from 23 public and private organizations in Delta State, Nigeria. The participants were made of 102 (52.31%) females and 93 (47.69%) males, with a mean age of 37.82 (SD = 6.71). Simple regression analysis revealed that employee work motivation positively and significantly predicted personnel’s work performance. Mediation analysis revealed that job satisfaction partially mediates the relationship while job stress was a significant moderator of the relationship. It was concluded that the employee’s work motivation influences their work performance partially through their satisfaction with their jobs and the relationship can be strengthened or weakened by feelings of stress. It was recommended that for the successful deployment of motivational strategies to enhance work performance, managers should select those strategies that have proven to be satisfying to employees as well as reduce work stressors.